ಕನ್ನಡ ಉನ್ನತ ಹಂತದ ಪಠ್ಯಪುಸ್ತಕ - (:unkn) unknown (My University, 2019)
This volume is the heterogeneous groups of learners is an attempt to develop an interest in the literature of Kannada language. The focus of this book is to develop creativity among the learners and it exploits the thematic content of the material available and extends it further. For this Purpose an atempt has been made in this text book to provide regional & social variations, contextual meanings, binary opposites and meanings with elaborate explanatory notes on cultural aspects wherever necessary.This text book helps the learners to feel ease, and develop confidence in language skills and provides learners to achieve communicative intent.
Kannada Advanced Course Text Book
Keywords: Kannada